2019
DOI: 10.3384/diss.diva-160918
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Decision after Anterior Cruciate Ligament Injury, and Evaluation of Measurement Properties of a Patient Reported Outcome Measure

Abstract: Background: After an ACL injury, treatment aims to restore knee function. Evaluation of treatment progress is important, and adequate measurement methods are necessary. The International Knee Documentation Committee-Subjective Knee Form (IKDC-SKF) is a common patient-reported outcome measure (PROM) used after ACL injury. It evaluates symptoms, function and physical activity. The IKDC-SKF had not been translated to Swedish language for use in Swedish clinical and research settings. The measurement properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(184 reference statements)
0
2
0
Order By: Relevance
“…The reasons for deciding on ACLR after 3 months was both knee joint instability and high activity demands. 38 Self-reported function and activity participation may have been influenced by the surgery. Most participants with ACL injury also reported that they were completing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for deciding on ACLR after 3 months was both knee joint instability and high activity demands. 38 Self-reported function and activity participation may have been influenced by the surgery. Most participants with ACL injury also reported that they were completing rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment choice is based on the patient's symptoms, type of injury to the ligament, examination, the growth remaining in his or her growth plates, and activity goals [5][6].…”
Section: Treatmentmentioning
confidence: 99%